Antismoking Ads at the Point of Sale: The Influence of Ad Type and Context on Ad Reactions. Issue 6 (3rd June 2017) - Kim, Annice; Nonnemaker, James; Guillory, Jamie; Shafer, Paul; Parvanta, Sarah; Holloway, John; Farrelly, Matthew
Abstract : Efforts are underway to educate consumers about the dangers of smoking at the point of sale (POS). Research is limited about the efficacy of POS antismoking ads to guide campaign development. This study experimentally tests whether the type of antismoking ad and the context in which ads are viewed influence people's reactions to the ads. A national convenience sample of 7, 812 adult current smokers and recent quitters was randomized to 1 of 39 conditions. Participants viewed one of the four types of antismoking ads (negative health consequences—graphic, negative social consequences—intended emotive, benefits of quitting—informational, benefits of quitting—graphic) in one of the three contexts (alone, next to a cigarette ad, POS tobacco display). We assessed participants' reactions to the ads, including perceived effectiveness, negative emotion, affective dissonance, and motivational reaction. Graphic ads elicited more negative emotion and affective dissonance than benefits of quitting ads. Graphic ads elicited higher perceived effectiveness and more affective dissonance than intended emotive ads. Antismoking ads fared best when viewed alone, and graphic ads were least influenced by the context in which they were viewed. These results suggest that in developing POS campaigns, it is important to consider the competitive pro-tobacco context in which antismoking ads will be viewed.